Do ethical concerns and personal values influence the purchase intention of fast-fashion clothing?. Issue 1 (23rd March 2020) - Stringer, Tara; Mortimer, Gary; Payne, Alice Ruth
Abstract : Purpose: The rise of fast fashion has changed the face of global fashion. Despite sector growth, critics have questioned the level of obsolescence, encouragement of over-consumption and fast fashion's unsustainable business practices. Specifically, mounting concerns surround the impact on environmental, worker and animal welfare. Accordingly, the aim of this current work is to understand the influence of consumer's values on ethical consumption in a fast-fashion context. Design/methodology/approach: An online survey was designed to collect responses relating to personal values and ethical concerns towards animal and worker welfare issues, as well as environmental concerns. A total of 350 US-based fast-fashion consumers completed the survey via Amazon MTurk. Factor analyses and structural equation modelling were used to analyse and test a theoretically hypothesised model. Findings: This study found that self-transcendence values and openness to change values have a positive impact on consumers' levels of ethical concern towards animal welfare, the environment and worker welfare concerns within the fashion industry. Furthermore, a consumer's level of concern towards animal welfare and the environment positively influences a consumer's likeliness to purchase ethically marketed fast fashion. Originality/value: This is the first study to investigate the role of consumer values and their influence on ethical concerns within the fashion industry and the impact of these concerns on intentions to purchase ethically marketed fast fashion. Responding to calls for further research into ethical consumption of apparel, this study includes all elements of ethical consumption identified, including animal welfare. This study identifies ethical areas of concern salient amongst fast-fashion consumers and provides a deeper understanding of the values impacting the level of ethical concerns surrounding animal welfare, the environment and worker welfare.